Comparison of blood metal ion levels in scoliosis patients following instrumented spinal fusion with cobalt-chromium and titanium alloy rods - Shota Tamagawa; Hidetoshi Nojiri; Tatsuya Sato; Takehisa Matsukawa; Yasuhiro Homma; Hiromitsu Takano; Muneaki Ishijima (Scientific Reports)
Abstract Elevated blood metal ion levels have been reported in patients following instrumented spinal fusion. However, the relationship between blood metal ion levels and clinical and radiographic outcomes remains elusive. The purpose of this study was to compare blood metal ion levels in patients with scoliosis undergoing corrective fusion surgery utilizing either cobalt-chromium (CoCr) or titanium (Ti) alloy rods, as well as preoperative scoliosis patients. Additionally, we investigated patient- and surgery-related factors associated with blood metal ion levels. This retrospective cohort study included 59 patients with CoCr rods (CoCr group), 29 patients with Ti alloy rods (Ti group), and 17 preoperative patients (control group). Blood samples were collected at a mean of 63 months postoperatively for the CoCr group and 113 months postoperatively for the Ti group. Blood levels of Co, Cr, and Ti were measured by inductively coupled plasma mass spectrometry. Blood Co levels were significantly elevated in the CoCr group compared to the control group (p = 0.021), with no significant difference observed between the CoCr and Ti groups (CoCr group: 0.28 μg/L, Ti group: 0.21 μg/L, control group: 0.20 μg/L). However, blood Cr and Ti levels were found to be below the limit of quantification in all 105 individuals. Furthermore, a significant negative correlation was observed between blood Co levels and the postoperative follow-up duration. These findings underscore the medium-term safety rather than the concerns regarding blood metal ion levels following corrective fusion for scoliosis; however, prolonged and meticulous follow-up is imperative.